2018
DOI: 10.5935/2595-0118.20180048
|View full text |Cite
|
Sign up to set email alerts
|

Pain, click and crepitation as factors associated with temporomandibular dysfunction in Parkinson’s disease

Abstract: BACKGROUND AND OBJECTIVES: Parkinson's disease leads to mandibular movements that affect the masticatory cycle and induce orofacial pain, one of the main clinical alterations found in temporomandibular dysfunction. Thus, the present study aimed to analyze the possible factors associated with temporomandibular dysfunction and to verify the frequency of the dysfunction in this population. METHODS: This was a cross-sectional study in which the participants were evaluated using the Diagnostic Criteria for Temporom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(38 reference statements)
1
5
1
Order By: Relevance
“…It was observed that people that reported this clinical sign were 2.27 times more likely to develop TMD. Such a particularity differs from a recent investigation with a similar sample, which observed that uncomfortable/ non-habitual bite was not related to TMD 16 . It agrees, though, with Trize et al 32 in a study involving 102 people aged 19 to 86 years and using the RDC/TMD to reach a diagnosis; they assessed that discomfort when biting is significantly associated with TMD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was observed that people that reported this clinical sign were 2.27 times more likely to develop TMD. Such a particularity differs from a recent investigation with a similar sample, which observed that uncomfortable/ non-habitual bite was not related to TMD 16 . It agrees, though, with Trize et al 32 in a study involving 102 people aged 19 to 86 years and using the RDC/TMD to reach a diagnosis; they assessed that discomfort when biting is significantly associated with TMD.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study pointed out the factors associated with TMD in older adults, namely: being female, having a low income, tinnitus, dizziness, depression, headache, or bruxism, missing teeth, and wearing complete dentures 10 . Moreover, pain, clicking, and crepitation have already been verified as factors associated with TMD in people with PD 16 . Hence, this study aimed to analyze the predictors of TMD in people with PD, verifying their association with sociodemographic aspects and stages of the disease to furnish further information in this field of knowledge.…”
Section: Introductionmentioning
confidence: 90%
“…This predominance was also described in the analysis of motor symptoms of Parkinson's disease carried out at a tertiary hospital in Rio de Janeiro, Brazil, in which there was a proportion of 2.5 men for every 1 woman in a total of 95 patients [22]. Therefore, this explains the contradiction observed from relating only elderly individuals to TMD or to depression, in which the authors highlighted the prevalence of the female sex in the analyses [3,14,[23][24][25].…”
Section: Discussionmentioning
confidence: 68%
“…including PD [3,4]. Moreover, in a study conducted by Magalhães et al [26], in which social classes were analyzed as risk factors for TMD, it was observed that the individuals that expressed more symptoms belonged to classes D and E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation